El Excentrico, 1976-04-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, CA, 2024)
April 20, 1976 [20 de abril de 1976]. Ano 27, No 2. Cover contains a photo of people from an indigenous tribe performing a traditional dance for the Cinco de Mayo celebration. This celebration would take place on May 2, 1976 at the Santa Clara County Fairgrounds.